Life Cycle and Matrix Analyses for Re-refined Oil in Japan. - Nakaniwa, Chie
Unstable market systems and consumer preferences for virgin oil have inhibited the development of waste oil re-refining in Japan. In this paper, comparative life cycle inventories were developed for re-refining waste oil and for the no refining waste case in which the waste oil is incinerated and needs are supplied with virgin oil. Total energy, CO2, NOx and SO2 emissions were included during the re-refining and consumption (incineration) stages; all are lower in the case of re-refined fuel use. In addition, by using a streamlined LCA matrix, we demonstrate that re-refining waste oil can reduce environmental impacts compared with the case in which virgin oil is chosen.
Keywords: Japan; LCA; LCI; Life cycle inventory; Life cycle assessment; Oil; Recycling; Refined oil; Streamlined LCA; Waste oil